Instability of the Northeast Greenland Ice Stream over the last 45,000 years - Nicolaj K. Larsen (Nature Portfolio, 2018)
The outlet glaciers that comprise the Northeast Greenland Ice Stream (NEGIS) have experienced accelerated retreat in recent years, yet their longterm stability remains unclear. Here, via cosmogenic surface exposure and radiocarbon ages, the authors investigate the stability of the NEGIS for the past 45 kyr.